A Systematic Review of Emerging Therapeutic Strategies in the Management of Chemical Injuries of the Ocular Surface. Issue 6 (November 2020) - Poon, Stephanie Hiu Ling; Wong, William Ho Lam; Bu, Yashan; Lo, Amy Cheuk Yin; Jhanji, Vishal; Chan, Yau Kei; Shih, Kendrick Co
Abstract : Objectives: To evaluate recent in vivo studies on emerging therapies for managing corneal epithelial injuries. Methods: The search was conducted on PubMed for articles published between January 2015 and September 2019 and in English language. Results: Thirty studies were identified for evaluation, including those on mesenchymal stem cells, amniotic membrane-derived therapies, endogenous peptides and their inhibitors, as well as hydrogel therapies. Intermediate to strong levels of evidence are presented regarding the use of these strategies on chemically injured cornea, including their effects on healing of corneal epithelial defect, anti-inflammatory properties, prevention of corneal neovascularization, as well as restoration of anatomy and functions of the anterior eye, although clinical trials are needed to determine the safety and efficacy of these strategies on humans. Conclusion: Recent advances and understanding in various novel therapeutic methods for corneal epithelial chemical injuries should provide potential alternatives to current standard treatment regimens and help reduce risks of complications, hence improve patient outcomes.